Implementasi Prinsip Good Governance dalam Pelayanan Publik di Kecamatan Johar Baru: Hambatan dan Strategi Peningkatan - Saputra, Munir; Prasetiyani, Erni (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
This study aims to analyze the implementation of Good Governance principles in public services in Johar Baru District, Central Jakarta. The main focus of this research is to identify the barriers encountered in the application of Good Governance principles and to formulate strategies to improve the quality of public services. The research method used is a descriptive qualitative approach with data collection through in-depth interviews, field observations, and documentation studies. The results of the study indicate that although Good Governance principles have been implemented, significant barriers remain, including limitations in human resources (HR), low public participation, and limited technology utilization. The recommended improvement strategies include enhancing HR capacity through training, maximizing the use of information technology, and strengthening mechanisms for accountability and public participation